Inhibition of miR30a-3p by sulforaphane enhances gap junction intercellular communication in pancreatic cancer. (28th January 2020) - Georgikou, Christina; Yin, Libo; Gladkich, Jury; Xiao, Xi; Sticht, Carsten; Torre, Carolina de la; Gretz, Norbert; Gross, Wolfgang; Schäfer, Michael; Karakhanova, Svetlana; Herr, Ingrid
Abstract: The therapy resistance of pancreatic cancer is associated with the loss of gap junction intercellular communication and connexin 43 expression. The broccoli isothiocyanate sulforaphane restored these features and therapy sensitivity. We investigated whether microRNA signaling is involved. Established cell lines and a patient tissue array (n = 96) were evaluated by miRNA and gene array, bioinformatics, expression studies, in situ hybridization and immunohistochemistry. Sulforaphane inhibited the expression of our top candidate miR30a-3p. Upon transfection of miR30a-3p inhibitors, the gemcitabine bystander effect, Cx43 expression and intercellular communication increased, whereas miR30a-3p mimics inhibited the luciferase activity of a Cx43 3′-UTR construct. miR30a-3p-overexpressing tumor xenografts had a decreased tumor volume and increased gemcitabine sensitivity. In patient tissues, a higher expression of miR30a-3p and a lower expression of Cx43 correlated with malignancy. These findings provide new knowledge and suggest sulforaphane as cotreatment for pancreatic cancer. Highlights: The bioactive broccoli-derived agent sulforaphane restores defective gap junction intercellular communication and Cx43 expression in PDA. Sulforaphane inhibits miR-365a-3p expression. miR-365 binds to the Cx43 3′UTR to inhibit Cx43 expression. Mechanistically, sulforaphane restores Cx43 expression, gap junction intercellular communication and the gemcitabine bystander effect by downregulation of miR-365a-3p.